2007
DOI: 10.1111/j.1460-9568.2007.05533.x
|View full text |Cite
|
Sign up to set email alerts
|

GABAergic mechanisms in absence epilepsy: a computational model of absence epilepsy simulating spike and wave discharges after vigabatrin in WAG/Rij rats

Abstract: In this study, the effects of vigabatrin on spike-and-wave discharges (SWDs) were measured in WAG/Rij rats, an animal model of absence epilepsy. Vigabatrin was used with the aim of enhancing GABAergic neurotransmission, and in this way to investigate the role of this process in the properties of SWDs. The study was carried out both in the rat, in vivo, and also using a computational model, in order to test different mechanisms that may account for the changes in SWDs after vigabatrin. The model parameters, rep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
12
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 33 publications
2
12
0
Order By: Relevance
“…Such a re-initiation attempt of the somatosensory cortex might be in accordance with signal analytical results (Maris et al (2006), Bouwman et al (2007)) showing that the chance of getting a new SWD is highest immediately after the previous one. In addition, it seems also to be in line with the above mentioned repetition of SWD frequency modulation that has been found for WAG/Rij rats and in patients during long lasting SWDs (Bosnyakova et al, 2006(Bosnyakova et al, , 2007.…”
Section: Interpretation Of Resultssupporting
confidence: 68%
“…Such a re-initiation attempt of the somatosensory cortex might be in accordance with signal analytical results (Maris et al (2006), Bouwman et al (2007)) showing that the chance of getting a new SWD is highest immediately after the previous one. In addition, it seems also to be in line with the above mentioned repetition of SWD frequency modulation that has been found for WAG/Rij rats and in patients during long lasting SWDs (Bosnyakova et al, 2006(Bosnyakova et al, , 2007.…”
Section: Interpretation Of Resultssupporting
confidence: 68%
“…Interestingly, it has been suggested that the balance between GABA A (Cl -) and GABA B (K + )-mediated conductances is essential for the control of SWDs (Kaminski et al, 2001;Marescaux et al, 1992b;Vergnes et al, 1984). The peak frequency of SWDs might be mainly determined by favoring the balance between GABA A and GABA B conductances towards GABA B neurotransmission (Bouwman et al, 2007a;Destexhe and Sejnowski, 2003). Different studies indicate that in TC neurons during absence seizures, (1) GABA A -mediated events are recruited with each SWD, (2) SWD-related activity can be evoked with no significant contribution of GABA B receptors, and (3) blockade of GABA A receptors potentiates SWDrelated activity, presumably through an indirect effect mediated by GABA B receptors (Staak and Pape, 2001).…”
Section: Gabamentioning
confidence: 99%
“…Mean-field models have a long history in computational neuroscience (e.g., [26][27][28][29], including many important applications for seizure modeling. These include, for example, mean-field models of absence seizures (30)(31)(32), of depth and surface electrode recordings from patients with temporal lobe epilepsy (33,34), seizure generalization (35), and anesthetic-induced seizures (36).…”
Section: Signatures Of a Critical Transition In A Mean-field Model Ofmentioning
confidence: 99%